The many faces of Atypical fibroxanthoma - Agaimy, Abbas (Seminars in Diagnostic Pathology, 2023)
Atypical fibroxanthoma (AFX) is an uncommon, primary dermal neoplasm of uncertain histogenesis, typically originating in the sun-damage skin of the head and neck of the elderly. Since first description in 1958, ∼3000 cases have been reported in the literature. However, the disease is underreported as the neoplasm is considered a standard diagnosis in the last decades. On the other hand, many earlier reports likely have included non-AFX mimics or aggressive pleomorphic dermal sarcomas. In contrast to its alarming high-grade histology, AFX behaves indolently with rare recurrences/ metastatic rate of <2%. The overall 10- and 20-year disease-specific survival rates are ∼ 100% and 98%, respectively. Histologically, AFX displays undifferentiated pleomorphic spindle cell morphology akin to undifferentiated pleomorphic sarcoma (UPS), a feature that was the basis of the abandoned historical terminology “MFH of skin”. However, in contrast to other undifferentiated sarcomatoid neoplasms, AFX is notorious for its highly variable histology with a plethora of patterns, underlining a wide differential diagnosis. Notably, spindle cell, keloid-like, pleomorphic, epithelioid, rhabdoid, clear cell, foamy cell, granular cell, bizarre cell, pseudoangiomatous, inflammatory, osteoclast-rich, and many others have been recognized with varying frequencies. Immunohistochemically, AFX is characterized by nonspecific profile with block-type expression of CD10 and aberrant p53 pattern and lack of pankeratin and other lineage-specific epithelial, mesenchymal, melanocytic and hematolymphoid markers. Sarcomatoid melanoma, spindle cell carcinoma and cutaneous anaplastic large cell lymphoma are major considerations. Distinction of AFX from pleomorphic dermal sarcoma (PDS) is arbitrary and is based on presence of ≥ 1 of four unfavorable histological features: more than minimal subcutaneous involvement, coagulative necrosis, lymphovascular invasion and perineurial invasion.
CRIS-Team Scopus Importer:2023-07-21
Keywords: BRAF; Dedifferentiated; Molecular testing; Sarcoma; Skin; TERT mutations